Settlement of Dispute on Murabahah Financing with Default Customer - Nawir Yuslem; Mhd. Yadhi Harahap; Darmansyah Hasibuan (Sultang Agung Islamic University, 2021)
This research is an Islamic law research that discusses the settlement of murabahah financing disputes with defaulting customers with a case study on the Supreme Court of the Republic of Indonesia Number: 649 K/AG Year 2017. The research model (mode of inquiry) of this study is qualitative. The preliminary step in this research is a conceptual approach with normative legal research methods. This study uses the theory of mashlahah: applicative theory is used in analyzing the data of this study and in the end this study shows that there is still a deviation between the provisions of murabahah financing and the concept of fiqh but to avoid this deviation, the wakalah system is made. The Supreme Court's decision Number 649 K/AG/2017 does not reflect a fully progressive decision, for the bank and also for the customer, the decision has not received a value of benefit, because the Supreme Court judge does not give a time limit to customers who are considered unable to make payments in accordance with the agreement (default) to reschedule (rescheduling), in the absence of such a time limit, provides an opportunity for customers who are in default to prolong the delay in payment so that this can be detrimental to the bank.